Plumericin prevents intestinal inflammation and oxidative stress in vitro and in vivo. Issue 1 (2nd December 2019) - Rapa, Shara F.; Waltenberger, Birgit; Di Paola, Rosanna; Adesso, Simona; Siracusa, Rosalba; Peritore, Alessio F.; D'Amico, Ramona; Autore, Giuseppina; Cuzzocrea, Salvatore; Stuppner, Hermann; Marzocco, Stefania
Abstract: Inflammatory bowel diseases (IBDs) are characterized by an inflammatory and oxidative stress condition in the intestinal tissue. In this study, we evaluated the effect of plumericin, one of the main bioactive components of Himatanthus sucuuba (Woodson) bark, on intestinal inflammation and oxidative stress, both in vitro and in vivo. The effect of plumericin (0.5‐2 µM) in vitro was evaluated in rat intestinal epithelial cells (IEC‐6) treated with lipopolysaccharides from E. coli (10 μg/mL) plus interferon‐γ (10 U/mL). Moreover, a 2, 4, 6‐dinitrobenzene sulfonic acid (DNBS)‐induced colitis model was used to evaluate the anti‐inflammatory and antioxidant activity of plumericin (3 mg/kg) in vivo. The results showed that plumericin significantly reduces intestinal inflammatory factors such as tumor necrosis factor‐α, cyclooxygenase‐2 and inducible nitric oxide synthase expression, and nitrotyrosine formation. Plumericin also inhibited nuclear factor‐κB translocation, reactive oxygen species (ROS) release, and inflammasome activation. Moreover, plumericin activated the nuclear factor erythroid‐derived 2 pathway in IEC‐6. Using the DNBS‐induced colitis model, a significant reduction in the weight loss and in the development of the macroscopic and histologic signs of colon injury, together with a reduced inflammatory and oxidative stress state, were observed in plumericin‐treated mice. These results indicate that plumericin exerts a strong anti‐inflammatory and antioxidant activity. Thus, it might be a candidate for the development of a new pharmacologic approach for IBDs treatment.